Assessing the Impact of Service Quality Dimensions on Customer Satisfaction in Southeast Asia’s Low-Cost Airline Industry - Ainul Mohsein Binti Abdul Mohsin; Anees Jane Ali; Nor Fazlina Binti Faisal Ansori; Nor Qurratul Najwa Binti Zulkifli; Norazirah Binti Johari; Norfarizazetie Binti Zainal; Norfatihah Binti Abdul Aziz; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Customer satisfaction has become a crucial determinant of success and sustainability for low-cost airlines in Southeast Asia, particularly in the post-pandemic era. This study aims to analyze how service quality dimensions (tangibility, reliability, responsiveness, assurance, and empathy) influence passenger satisfaction within the low-cost aviation sector. A quantitative research design was employed using survey data collected from 175 AirAsia passengers. Data were analyzed through descriptive and multiple regression analysis. The model explains 42.5% of the variance in customer satisfaction (R² = 0.425), confirming the significant role of service quality in shaping passenger perceptions. Regression results reveal that empathy (? = 0.265, p 0.001) is the most influential factor, followed by tangibility (? = 0.233, p = 0.002) and reliability (? = 0.165, p = 0.047). Assurance (? = 0.159, p = 0.032) also exerts a positive, albeit smaller, effect. These findings affirm the applicability of the SERVQUAL model in the aviation context and underscore the strategic importance of improving interpersonal engagement, operational reliability, and service consistency. The study contributes theoretically by validating SERVQUAL in a cost-sensitive market and practically by offering insights to enhance passenger satisfaction in low-cost airlines